Electrodialysis membrane with concentration polarization – A review - Al-Amshawee, Sajjad; Mohd Yusri, Mohd Yunus (Elsevier Ltd, 2024)
Electrodialysis (ED) is more robust than reverse osmosis in terms of scaling, purity, and control, but its efficiency is dependent on concentration polarization. Concentration polarization is not only inherent in ED, but also commonly found in microfiltration, ultrafiltration, nanofiltration, reverse osmosis, and fuel cells with ion exchange membranes (IEMs). The current meta-synthesis review aims to identify the best approach for reducing concentration polarization, increasing velocity, or maximizing spacer design. Concentration polarization can significantly impact membrane capability and reduce overall performance. To reduce concentration polarization, innovative geometries and configurations of membrane spacers are needed. Carefully designed spacers that increase channel turbulence can help mitigate concentration polarization effects. However, advanced spacers still have negative consequences, such as the shadow effect, which reduces the ion exchange area and increases permeation resistance. Increasing the flowrate can improve membrane performance, maximize recovery/permeate rate, and reduce the limitations of spacer design. However, increasing the flowrate can have drawbacks in certain membrane applications. For example, a higher Reynolds number may improve spacer performance with a higher Sherwood number but at the cost of a greater power number. This review found that the extent of concentration polarization formation is heavily influenced by both spacer design and solution velocity. Convective motions affect mixing, making the concentration domain within the cell highly dependent on spacer design and flow velocity.